2012
DOI: 10.1039/c2ib20108a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for distinct mechanisms of uptake and antitumor activity of secretory phospholipase A2 responsive liposome in prostate cancer

Abstract: Secretory phospholipase A2 (sPLA2) cleave phospholipids at sn-2 ester bonds, releasing lysophospholipids and fatty acids, and are over expressed in several pathologies, including inflammation, arthritis, sepsis and breast and prostate cancers. Herein we evaluated the therapeutic activity of liposomes engineered to be responsive to different sPLA2 isoforms compared to clinically used long-circulating (pegylated) sterically stabilized liposomes (SSL) in vitro and in vivo, and assess differences in role of sPLA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Recent studies, including those from our own laboratory, have engineered liposomes to target pathologies that overexpress sPLA 2 and enhance the release of drugs at diseased tissue [87-89]. sPLA 2 -targeted nanoparticles are composed of phospholipids that are preferentially cleaved by sPLA 2 , such as those with negatively charged and altered levels of phospholipids containing other zwitterionic head groups and shorter fatty acyl chains [89-91].…”
Section: Therapies Targeting Spla2mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies, including those from our own laboratory, have engineered liposomes to target pathologies that overexpress sPLA 2 and enhance the release of drugs at diseased tissue [87-89]. sPLA 2 -targeted nanoparticles are composed of phospholipids that are preferentially cleaved by sPLA 2 , such as those with negatively charged and altered levels of phospholipids containing other zwitterionic head groups and shorter fatty acyl chains [89-91].…”
Section: Therapies Targeting Spla2mentioning
confidence: 99%
“…sPLA 2 -targeted nanoparticles are composed of phospholipids that are preferentially cleaved by sPLA 2 , such as those with negatively charged and altered levels of phospholipids containing other zwitterionic head groups and shorter fatty acyl chains [89-91]. This preference is likely a result of the many positively charge amino acids present in sPLA 2 ’s protein sequence (Figure 2B-D), especially at the ICS where these residues are believed to increase the interaction with the negatively charged phospholipid head group.…”
Section: Therapies Targeting Spla2mentioning
confidence: 99%
See 2 more Smart Citations
“…[199][200][201] Liposomes that are responsible for sPLA2 (SPRL) were engineered to facilitate liposomal degradation and drug release in tumor tissues. [202][203][204] In a study comparing the uptakes and cytotoxicities of the SPRL encapsulated with DOX and sterically stabilized liposomes encapsulated with DOX, Moch et al suggested that the efficacy of the sPLA2 liposomes are mediated by cell-dependent mechanisms. 203 Recently, Hofmann et al provided evidence supporting the existence of drug delivery into cells without cellular uptake of the nanoparticles through a new "kiss-andrun" mechanism between (polymeric) nanoparticles and the cell membrane.…”
mentioning
confidence: 99%